2014
DOI: 10.1161/circulationaha.114.009847
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Like Protein ISG15 (Interferon-Stimulated Gene of 15 kDa) in Host Defense Against Heart Failure in a Mouse Model of Virus-Induced Cardiomyopathy

Abstract: Background-Common causative agents in the development of inflammatory cardiomyopathy include cardiotropic viruses such as coxsackievirus B3 (CVB3). Here, we investigated the role of the ubiquitin-like modifier interferon-stimulated gene of 15 kDa (ISG15) in the pathogenesis of viral cardiomyopathy. Methods and Results-In CVB3-infected mice, the absence of protein modification with ISG15 was accompanied by a profound exacerbation of myocarditis and by a significant increase in mortality and heart failure. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
110
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 50 publications
3
110
1
2
Order By: Relevance
“…166 Furthermore, ablation of IFN stimulated gene 15 results in amplified virus yields and increased severity of myocarditis and mortality. 167 In addition to their function in extracellular matrix remodeling, [168][169][170][171] a critical process involved in the progression of myocarditis to DCM, matrix metalloproteinases also serve as important modulators of the antiviral immune response. A recent study has revealed a novel role for matrix metalloproteinase-12 in innate immunity via mediating the secretion of IFN-α by transcriptional regulation of inhibitor of kappa B alpha, alpha (IκBα).…”
Section: Immunopathogenesis Of Viral Myocarditismentioning
confidence: 99%
“…166 Furthermore, ablation of IFN stimulated gene 15 results in amplified virus yields and increased severity of myocarditis and mortality. 167 In addition to their function in extracellular matrix remodeling, [168][169][170][171] a critical process involved in the progression of myocarditis to DCM, matrix metalloproteinases also serve as important modulators of the antiviral immune response. A recent study has revealed a novel role for matrix metalloproteinase-12 in innate immunity via mediating the secretion of IFN-α by transcriptional regulation of inhibitor of kappa B alpha, alpha (IκBα).…”
Section: Immunopathogenesis Of Viral Myocarditismentioning
confidence: 99%
“…Additionally, it was shown that ISG15 is also crucial for the control of coxsackievirus B3 (CBV3) infections, which induce myocarditis. Concordantly, CBV3-infected USP18 C61A/C61A cardiomyocytes, which showed increased ISGylation, exhibited smaller myocarditis foci during CVB3 myocarditis [14].…”
mentioning
confidence: 78%
“…Additionally, it was shown that ISG15 is also crucial for the control of coxsackievirus B3 (CBV3) infections, which induce myocarditis. Concordantly, CBV3-infected USP18 C61A/C61A cardiomyocytes, which showed increased ISGylation, exhibited smaller myocarditis foci during CVB3 myocarditis [14].Since the selective genetically inactivation of the protease activity did not lead to detrimental defects, small molecule inhibition of the protease activity of USP18 could constitute a novel, well-tolerated strategy for anti-viral intervention strategies. The USP18 C61A/C61A mouse represents an excellent system to evaluate the potential benefits and consequences of such an approach in different infection and cancer models.…”
mentioning
confidence: 92%
“…A subsequent study demonstrated the protective role of ISG15 in myocyte damage during myocarditis. CVB3-infected ISG15 deficient mice developed larger foci with cardiomyocyte death and increased infiltration of inflammatory cells, compared to wild-type mice [112]. These pathological changes were in line with marked deterioration of left ventricle function and eventually increased mortality of ISG15 deficient mice post viral infection.…”
Section: Isg15mentioning
confidence: 93%
“…Consistently, Ube1L-deficient mice infected with CVB3 displayed more myocyte damage compared to the wild-type mice. In contrast, USP18 C61A/C61A knock-in mice, in which ISGylated proteins were stabilized due to inactivation of ISG15-specific isopeptidase activity, displayed reduced myocyte damage after CVB3 infection [112]. CVB3-protease 2A (2Apro) interferes with host cell translation by cleaving the host protein eIF4G and is identified as one of the ISG15 targets.…”
Section: Isg15mentioning
confidence: 99%